The deoxyribonucleic acid modification enzyme of bacteriophage P1. Subunit structure - Brockes, Jeremy P. (1973)
The bacteriophage P1 modification enzyme was purified 1400-fold from induced lysogens of a thermoinducible mutant of bacteriophage P1. The most purified fraction, when analysed by polyacrylamide-gel electrophoresis in sodium dodecyl sulphate, showed two principal stained bands. The two bands co-sedimented in a glycerol gradient with the modification activity, at a rate which, when compared with the rate of sedimentation of marker proteins, corresponds to a sedimentation coefficient in water of 6S. The mobilities of the bands on sodium dodecyl sulphate–polyacrylamide-gel electrophoresis corresponded to polypeptides of molecular weight 70000 and 45000 and they were present in equimolar amounts. It was concluded that the 6S species of the enzyme is a dimer of unlike subunits.